Laporan Kegiatan Pengabdian Masyarakat Pemberdayaan Ekonomi Perempuan HKBP Ressort Medan Sunggal - Hanna Meilani Damanik; Martin Luter Purba; Hendrik E. S Samosir (Jurnal Visi Pengabdian Kepada Masyarakat, 2021)
The aims of this service is to help the women of the HKBP Ressort Medan Sunggal to understand the importance of economic empowerment and practical things that can be done in the context of empowerment. The activity was carried out in the form of a lecture or seminar which was attended by 23 members of the HKBP Ressort Medan Sunggal congregation. We hope, by this activity, the participant of the seminar has new mindset about the importance of women in the context of the household and church and then can generate ideas and motivation also to develop the economic activities in small business enterprise that can empower women both individually or in groups and gain description of the forms of activities that can be carried out economically and understand various alternative sources of funding for these activities.